Abyssocladia mucronata Vacelet 2020, sp. nov. - Vacelet, Jean (Zenodo, 2020)
Abyssocladia mucronata sp. nov. (Figs 7–8) Holotype MNHN-IP-2015-1475 KANACONO Expedition, New Caledonia (MEOW), Station beam trawl CP4754, 25/08/2016, 23°22’S 167°54’E, 1009–1019 m. Paratype 1: MNHN-IP-2015-1476, same data as holotype. Paratype 2 : MNHN-IP-2015-1477, same data as holotype. Paratype 3 : MNHN-IP-2015-1478, same data as holotype. Additional specimens . Six specimens and numerous fragments, same data as the holotype. Pictures of freshly collected and in situ specimens from KANADEEP Expedition 2, New Caledonia, 16/09/2019, PL 744-05, BB-C-16, Mont Munida. Diagnosis. Branching, arborescent Cladorhizidae with mucronate styles, mucronate anisotornotes, and arcuate cleistochelae with intermingling appendages. Description. Ten specimens and numerous fragments of an arborescent, dichotomously branching sponge with a cylindrical stem dividing into several branches in a single plane with an angle of approximately 45°, up to 16 cm high and 12 cm wide (Figs 7 A–D). The branches, up to 30 in number, are straight or weakly curved. On living specimens observed in situ, the branches bear regular low lobes, giving a corrugated, ringed appearance (Fig 7C). These low lobes are less visible on freshly collected, still living specimens, and disappear on preserved specimens which have an irregular surface, certainly due to poor preservation (Fig 7A). The cylindrical stem before the first branches is smooth, 20–35 mm long by 3–6 mm in diameter, with faint, weakly spiraled nervures on the surface, 200–250 µm in diameter (Fig 7F), corresponding to the spicule fascicles of the stem. The sponge was attached to a rocky bottom by a hard, conic holdfast disk 6–14 mm in diameter. The color, brown in ethanol, is yellow in living specimens. Skeleton. The holdfast of the attachment base is made of mucronate styles 1, closely apposed and parallelly arranged in a compact, dense skeleton, often including small pieces of rock. The basal stem and the axis of the branches are made of the same mucronate styles, longitudinally included in spongin in a polyaxial skeleton of fibers about 200 µm in diameter. These fascicles of spicules appear as weakly spiraled nervures at the surface of the stem. In the branches, the mucronate styles 1 of the axis are more regular in size than in the stem and base. On both sides of the branches, the verrucose or warty expansions, which are present only in places in the preserved specimens, have a secondary axis of mucronate oxea, thinner than the styles 1, perpendicularly or obliquely inserted in the main axis, ca 100 µm in diameter. Abyssochelae are most often irregularly dispersed in the tissue of the expansions, are rarely grouped without definite order at their surface, and are absent from the stem and the attachment base. In all specimens, the living tissue of the surface seems to be poorly preserved. Spicules (Fig 8). Mucronate styles or pseudoxeas (Figs 8B, C): one end (the “head”) has a short, mucronate point which is sometimes twisted and rarely absent; the other end has a longer, non-mucronate point. In the branches and in the stem, these spicules are straight or more rarely weakly curved, slightly fusiform, and regular in size: 510– 660 x 15–19 µm (Fig 8B). In the attachment base, they are considerably more variable in shape and size, sometimes short and thick, slightly curved and more often non-mucronate: 160–570 x 13–19 µm (Fig 8C). The short styles are more or less numerous according to the specimen and the location in the holdfast. Anisotornotes (Fig 8D), are straight and isodiametric, ending in short, mucronate points. The two ends are most often slightly different. They are mainly found in the short, secondary axis of the lateral expansions of the branches. They are absent from the attachment base and rare in the axis of stem and branches. 310–360 x 5–7.5 µm. Arcuate cleistochelae of unusual shape (Fig 8E). The lateral alae and the frontal tooth of both ends cross each other and become strongly entangled. Diverse stages of the growth and intermingling of the alae and teeth are present (Fig 8F), with the alae initially falciform, then thickening and becoming angulate and enlarged at their end. 38–45 x 15–20 µm with a height/width ratio around 2–2.5. Living tissue and reproductive elements . On the preserved specimens, living tissue is irregularly verrucose, with occasional rare, short bud-like processes that are irregular and less than 1 mm long. The main stem has no flesh coating. In all parts, the living tissue contains a great number of foreign bodies, including foraminiferous shells, foreign spicules of synascidians and hexactinellids (Fig 7E). It is unknown if these foreign bodies are present in the living specimens. No cellular elements can be described in the living tissue, and no reproductive element were observed. No aperture or aquiferous system was visible. No clearly identified prey was observed. Distribution and Ecology. All examined specimens were collected by trawl from 1009–1019 m depth, 23°22’S 167°54’E, Station CP 4734 SE of New Caledonia, during the KANACONO expedition, during the same operation that found Abyssocladia microstrongylata nov. sp. The number of specimens obtained in this single trawling operation suggested that the sponge was rather abundant at this location, and it appears to be the same for the new collection and in situ observation made possible during the KANADEEP 2 expedition in 2019 in station PL 744-05 at a distance of approximately 50 km. The enlarged, solid fixation base indicates that the sponge was living on rocky substrate, a fact confirmed by in situ observation. Etymology. From latin mucronatus, referring to the mucronate character of the megascleres. Remarks . This new species is remarkable due to several characteristics. Owing to its external shape, which is constant in all the specimens, it resembles a gorgonian more than a sponge. Such an arborescent shape has been described in other Cladorhizidae such as Asbestopluma (Asbestopluma) desmophora Kelly & Vacelet, 2011, or A. (A.) monticola Lundsten, Reiswig & Austin, 2014 but these belong to another genus with different spicules, and bear some filaments on the branches. Two specimens of Cladorhizidae from the KANADEEP collection, n° 1764 A, 7 cm high, have a very similar external shape and color, with an inflated holdfast at the base, but have the spiculation of the genus Cladorhiza . They could easily be confused in the field by their external characteristics, although on close examination, they differ by the presence of small filaments on the terminal part of the branches. Filaments, frequently observed in Cladorhizidae, are absent here in A. mucronata sp. nov. and seem to be absent in the living or well preserved specimens. The new species is also well characterized by its spicules. The megascleres are unique among Cladorhizidae by their mucronate character. The larger spicules, which constitute the main axis, have different ends, as usual in styles, but the “head” is most often mucronate, different from that of the “tip”, so they are termed “mucronate styles”. The smaller megascleres, located mainly in the secondary axes, are considered as anisotornotes due to their shape and to their ends which are most often slightly different. Given their large height/width ratio of around 2–2.5, the chelae are here termed arcuate cleistochelae rather than abyssochelae, following Lopes et al . 2011. But this term is not entirely satisfactory, as cleistochelae applies to arcuate isochelae with the median teeth nearly in contact. Here the shape is very unusual, with both alae and teeth not only in contact, but intermingling and strongly entangled. There are many modified types of chelae in Poecilosclerida, especially in Mycalidae and Cladorhizidae, and some have long teeth and alae that more or less cross those of the other extremity. Examples could be the thaumatochela described in Mycale ( Navicula ) thaumatochela Lundbeck, 1905, the anisochelae of Mycale (Anomomycale) titubans (Schmidt, 1870) described by Lundbeck 1905, or the naviculochelae found in diverse Mycale (Naviculina) spp. But these belong to a different type of chelae, anisochelae, non isochelae as here. In arcuate isochelae, the chelae of Echinostylinos glomeris (Topsent, 1904), in Phellodermidae, have teeth and alae which cross, but which never intermingle as they do in this new Abyssocladia . Although this type of chela appears to be very unusual among arcuate isochelae, it appears unjustified to distinguish a special chelae term for them, which would be based on a single example. In this species, there is a remarkable number of chelae with appendages not fully entangled, interpreted as possible growing stages (Fig 8F). These special chelae raise an interesting question in a presumably carnivorous sponge, concerning the function of these spicules in trapping prey, a point which will be discussed in a general remark below. : Published as part of Vacelet, Jean, 2020, Carnivorous sponges (Porifera, Cladorhizidae) from the deep South Pacific (New Caledonia) with the description of three new species of the genus Abyssocladia and remarks on genus Cercicladia, pp. 257-276 in Zootaxa 4767 (2) on pages 269-272, DOI: 10.11646/zootaxa.4767.2.3, http://zenodo.org/record/3770819 : {"references": ["Kelly, M. & Vacelet, J. (2011) Three new remarkable carnivorous sponges (Porifera, Cladorhizidae) from deep New Zealand and Australian (Macquarie Island) waters. Zootaxa, 2976 (1), 55 - 68. https: // doi. org / 10.11646 / zootaxa. 2976.1.4", "Lundsten, L., Reiswig, H. & Austin, W. C. (2014) Four new species of Cladorhizidae (Porifera, Demospongiae, Poecilosclerida) from the Northeast Pacific. Zootaxa, 3786 (2), 101 - 123. https: // doi. org / 10.11646 / zootaxa. 3786.2.1", "Lopes, D. A., Bravo, A. & Hajdu, E. (2011) New carnivorous sponges (Cladorhizidae: Poecilosclerida: Demospongiae) from off Diego Ramirez Archipelago (south Chile), with comments on taxonomy and biogeography of the family. Invertebrate Systematics, 25, 407 - 443. https: // doi. org / 10.1071 / IS 11015", "Lundbeck, W. (1905) Porifera. (Part II.) Desmacidonidae (pars.). The Danish Ingolf-Expedition. 6 (2). BiancoLuno, Copenhagen, 1 - 219, pls. I-XX.", "Schmidt, O. (1870) Grundzuge einer Spongien-Fauna des Atlantishen Gebietes. Wilhelm Engelmann, Leipzig, 2 + 88 pp., VI pls. [pp. iii-iv + 1 - 88, pls. I-VI]", "Topsent, E. (1904) Spongiaires des Acores. Resultats des campagnes scientifiques accomplies par le Prince Albert I, Monaco, 25, 1 - 280, pls. 1 - 18. https: // doi. org / 10.5962 / bhl. title. 61852"]}